2018
DOI: 10.1038/s41598-018-33595-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the viable but non-culturable state in bacterial pathogens by household cleaners and inorganic salts

Abstract: Effective monitoring of microbial pathogens is essential for a successful preventive food safety and hygiene strategy. However, as most monitoring strategies are growth-based, these tests fail to detect pathogenic bacteria that have entered the viable but non-culturable (VBNC) state. The present study reports the induction of the VBNC state in five human pathogens by commercially available household cleaners in combination with inorganic salts. We determined that non-ionic surfactants, a common ingredient in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 32 publications
(35 reference statements)
1
43
0
Order By: Relevance
“…Induction and confirmation of the VBNC state was performed according to Robben et al (2018). One milliliter of early log phase bacteria (OD 600 : 0.6) was centrifuged for 5 min at 8,000 × g .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction and confirmation of the VBNC state was performed according to Robben et al (2018). One milliliter of early log phase bacteria (OD 600 : 0.6) was centrifuged for 5 min at 8,000 × g .…”
Section: Methodsmentioning
confidence: 99%
“…However, research has shown that large populations of VBNC cells also exist in unstressed environments, which appear to be a stochastic physiological transformation to protect a subpopulation of cells from unexpected stresses (Ayrapetyan et al, 2015; Gonçalves and de Carvalho, 2016). It has also been demonstrated that VBNC bacteria are able to resist a wide range of unfavorable conditions including starvation, temperature shifts, high or low pH and salinity, oxidative stress, cleaners, antimicrobial compounds, and antibiotics (Nowakowska and Oliver, 2013; Li et al, 2014; Zhao et al, 2017; Ayrapetyan et al, 2018; Robben et al, 2018). In addition, the accumulation of several non-toxic stresses has been shown to switch pathogens into the VBNC state (Overney et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the method thus detects living, dead, and viable but nonculturable cells (VBNCs). While detection of nongrowing cells in the past was often discussed as a disadvantage (1), increasing interest and awareness of VBNCs today highlight that nongrowing cells are also a potential threat (30). Further, the detection of nongrowing cells advantageously attests to badly cleansed areas, as most chemical disinfectants alone cannot remove DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the futility of normal culture plate technique often requires pre-enrichment, selective enrichment, selective plating and identifications. The sequence of the method is stereotyped, lengthy, time-consuming, limited by its low sensitivity -giving false-negative results even with the presence of viable but non-culturable (VBNC) cells [23,24]. Immunology-based methods present varying disadvantages such as the use of expensive test kits, false result due to cross-reactivity with closely related antigens, the need for pre-enrichment to attain detectable antigen level in samples.…”
Section: Limitations Of the Established Pathogen Detection Methodsmentioning
confidence: 99%